2011
DOI: 10.3390/rs3081553
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Buildings from True Color Stereo Aerial Images Using a Decision Making Strategy

Abstract: The automatic extraction of buildings from true color stereo aerial imagery in a dense built-up area is the main focus of this paper. Our approach strategy aimed at reducing the complexity of the image content by means of a three-step procedure combining reliable geospatial image analysis techniques. Even if it is a rudimentary first step towards a more general approach, the method presented proved useful in urban sprawl studies for rapid map production in flat area by retrieving indispensable information on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…One method is to use stereo Hr-ORSI pairs [80][81][82][83][84][85], and the other method is to use the shadows of buildings from a single Hr-ORSI [33,37,[86][87][88]. Earlier studies have shown that using stereo Hr-ORSI pairs results in more accurate height estimates.…”
Section: Determining Building Heightsmentioning
confidence: 99%
“…One method is to use stereo Hr-ORSI pairs [80][81][82][83][84][85], and the other method is to use the shadows of buildings from a single Hr-ORSI [33,37,[86][87][88]. Earlier studies have shown that using stereo Hr-ORSI pairs results in more accurate height estimates.…”
Section: Determining Building Heightsmentioning
confidence: 99%
“…As the proposed pre-processing comes in addition and not as a replacement for the suggested procedures in Blaschke et al [12], the aggregation remains valid while integrating the important feature attribute of single pixel objects at the lowest GEOBIA level and using the properties at higher aggregation levels. Urban mapping and single building detection is a common topic in GEOBIA [15], and the use of convolution and edge detection is regarded amongst the more important features in building detection [16]. The equation presented extends the already available list of features where the ability to apply the analysis to very large neighborhoods is related to a trend in the availability of increased hardware capacities.…”
Section: Agricultural Application With Urban Mapping Extensionsmentioning
confidence: 98%
“…The equation presented extends the already available list of features where the ability to apply the analysis to very large neighborhoods is related to a trend in the availability of increased hardware capacities. This is in addition to recent approaches in the domain of building detection that discuss the applications of edge detection and contrast analysis using limited window size on smaller neighborhoods only [16].…”
Section: Agricultural Application With Urban Mapping Extensionsmentioning
confidence: 99%
“…Useful spectral information on vegetation can be obtained from the RGB images by means of image transformations and band ratios [37,38]. In the first step, to verify whether spectral information based on a single pixel alone is effective in rural areas with widespread plastic covered vineyards, we used spectra of the six selected classes from ten randomly selected target points (mean DN values of the selected classes in all three RGB bands) to check they could be accurately discriminated.…”
Section: Classification Proceduresmentioning
confidence: 99%